Pendidikan Budi Pekerti di SMP: Penafsiran Ulang Ajaran Taman Siswa dalam Era Digital - Febi Filga Cantika; Siti Nuraeni; Ridha Anggara; Sri Wiwik Endang Witosari; Ricky Yoseptry (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2025)
The development of digital technology has transformed adolescents’ patterns of interaction and given rise to various violations of digital ethics, such as cyberbullying, the spread of hoaxes, and negative online postings. Consequently, schools need to develop character education that aligns with the demands of the times. This study aims to analyze the reinterpretation of Tamansiswa teachings, particularly Tri Karsa, in fostering digital ethics; to describe the mechanisms for handling violations at SMPN 2 Campaka; to identify challenges in implementing a restorative–pedagogical approach; and to evaluate students’ perceptions of the effectiveness of case handling. Using a qualitative method with a case study approach, data were collected through interviews, observations, and documentation, and then analyzed using the Miles, Huberman, and Saldaña model. The findings indicate that Tri Karsa is interpreted as critical digital literacy, digital empathy, and digital moral responsibility, while case handling prioritizes dialogue, mediation, and character development, although it is not yet supported by specific standard operating procedures. Several obstacles were identified, including limited teachers’ digital competence, resistance from Generation Z/Alpha students, minimal parental involvement, and limited ICT facilities. Nevertheless, students perceive the handling mechanisms as fairly just, educational, and having a positive impact on digital behavior. This study affirms the relevance of Tamansiswa values as a foundation for developing a Tamansiswa-based Digital Character Education Model to strengthen humanistic and contextual character education in the digital era.